True Precocious Puberty Following Treatment of a Leydig Cell Tumor: Two Case Reports and Literature Review - Verrotti, Alberto; Penta, Laura; Zenzeri, Letizia; Lucchetti, Laura; Giovenali, Paolo; De Feo, Pierpaolo (Frontiers in Pediatrics, 2015)
Leydig cell testicular tumors are a rare cause of precocious pseudopuberty in boys. Surgery is the main therapy and shows good overall prognosis. The physical signs of precocious puberty are expected to disappear shortly after surgical removal of the mass. We report two children, 7.5 and 7.7 year-old boys, who underwent testis-sparing surgery for a Leydig cell testicular tumor causing precocious pseudopuberty. During follow-up, after an immediate clinical and laboratory regression, both boys presented signs of precocious puberty and ultimately developed central precocious puberty. They were successfully treated with gonadotropin-releasing hormone (GnRH) analogs. Only six other cases have been described regarding the development of central precocious puberty after successful treatment of a Leydig cell tumor causing precocious pseudopuberty. Gonadotropin-dependent precocious puberty should be considered in children treated for a Leydig cell tumor presenting persistent or recurrent physical signs of puberty activation. In such cases, therapy with GnRH analogs appears to be the most effective medical treatment.